Enantioselective three-component coupling of heteroarenes, cycloalkenes and propargylic acetates - Teng, Shenghan (2021)
Asymmetric coupling proceeds efficiently between propargylic acetates, cycloalkenes and electron-rich heteroarenes including indoles, pyrroles, activated furans and thiophenes. 2,3-Disubstituted tetrahydrofurans and pyrrolidines are produced in trans configuration and excellent enantiomeric ratios. The reaction proceeds via Wacker-type attack of nucleophilic heteroarenes on alkenes activated by allenyl PdII species.